Acute intoxication due to Wisteria floribunda seed in seven young children. Issue 5 (9th March 2017) - Kim, Dongwan; Park, Jihyoung; Kim, Yun Mi; Tchah, Hann
Abstract: Background: Wisteria floribunda is a vine commonly found in Korea, Japan, and the USA. The objective of this observational study was to assess the toxicity of W. floribunda seeds in young children. Methods: Of 28 children in a kindergarten who participated in a field trip, seven ingested W. floribunda seeds: six half of the seed and one a whole seed. These seven children were admitted to the Gachon University Gil Medical Center in Incheon, Korea. Results: All of the children had vomiting within 4 h of ingesting the W. floribunda seed; the child who ingested a whole seed began to vomit 2 h after ingestion. By 5 h after ingestion, they all complained of abdominal pain and one child was lethargic. Leukocytosis was observed in all of the children. Abdominal pain and vomiting subsided in all of the children within 2 days after admission. The average duration of hospitalization was 3.1 days. Conclusions: W. floribunda seed ingestion induced gastrointestinal and neurologic symptoms in these young children. Given that the onset of vomiting was earlier in the child who ingested a whole seed than in the children who had ingested only a half, the amount of ingested seeds may be associated with the severity of the symptoms. Ingestion of half a raw W. floribunda seed can cause gastrointestinal symptoms in young children and even result in hospitalization.